Ethnoveterinary medicine in Asia : (International Institute of Rural Reconstruction, 1994)
This book introduce about Collaborating organizations, Participants and workshop staff, How to use this manual, Reduced appetite, Coughs and colds, Diarrhea, Intestinal worms, Ticks, lice and mites, Fungal diseases, nfectious diseases...